Mari Menulis Kreativitas Anak dalam Mengungkapkan Ide Melalui Tulisan - Nur Hasanah; Dila Eriska; Indri Angraini; Hotmian Situmorang; Juliati Juliati (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study delves into the fascinating interplay between creativity development, literacy-based learning, and the creative writing skills of young students. We all know that nurturing creativity in early childhood is crucial for shaping personality and cognitive growth. By tapping into local wisdom and integrating digital literacy technologies, the researchers have found that writing instruction becomes more engaging and meaningful for the students. The results are quite compelling - learning media that resonate with the students significantly boost their writing abilities while also shaping their character. This comprehensive study employs both qualitative and quantitative approaches, leaving no stone unturned in its quest to understand this dynamic process. The key takeaway? When we empower students with creativity-driven, tech-savvy instruction, their creative writing skills truly soar.